A late jet rebrightening revealed from multiwavelength monitoring of the black hole candidate XTE J1752-223 - Russell, D.; Curran, P.; Munoz-Darias, T.; Lewis, F.; Motta, S.; Stiele, H.; Belloni, T.; Miller-Jones, James; Jonker, P.; O'Brien, K.; Homan, J.; Casella, P.; et al. (Wiley-Blackwell Publishing Ltd., 2012)
We present optical monitoring of the black hole candidate XTE J1752−223 during its 2009–10 outburst and decay to quiescence. The optical light curve can be described by an exponential decay followed by a plateau, then a more rapid fade towards quiescence. The plateau appears to be due to an extra component of optical emission that brightens and then fades over ~40 days. We show evidence for the origin of this optical ‘flare’ to be the synchrotron jet during the decaying hard state, and we identify and isolate both disc and jet components in the spectral energy distributions. The optical flare has the same morphology and amplitude as a contemporaneous X-ray rebrightening. This suggests a common origin, but no firm conclusions can be made favouring or disfavouring the jet producing the X-ray flare. The quiescent optical magnitudes are B≥ 20.6, V≥ 21.1, R≥ 19.5, i′≥ 19.2. From the optical outburst amplitude we estimate a likely orbital period of <22 h. We also present near-infrared (NIR) photometry and polarimetry and rare mid-IR imaging (8–12 Graphicm) when the source is nearing quiescence. The fading jet component, and possibly the companion star, may contribute to the NIR flux. We derive deep mid-IR flux upper limits and NIR linear polarization upper limits. With the inclusion of radio data, we measure an almost flat jet spectral index between radio and optical; Fν∝ν∼+0.05. The data favour the jet break to optically thin emission to reside in the IR, but may shift to frequencies as high as the optical or UV during the peak of the flare.